High-Resolution Monitoring of Antimicrobial Consumption in Vietnamese Small-Scale Chicken Farms Highlights Discrepancies Between Study Metrics - Cuong, Nguyen Van; Phu, Doan Hoang; Van, Nguyen Thi Bich; Dinh Truong, Bao; Kiet, Bach Tuan; Hien, Bo Ve; Thu, Ho Thi Viet; Choisy, Marc; Padungtod, Pawin; Thwaites, Guy; Carrique-Mas, Juan (Frontiers in Veterinary Science, 2019)
Chicken is, among farmed species, the target of the highest levels of antimicrobial use (AMU). There are considerable knowledge gaps on how and when antimicrobials are used in commercial small-scale chicken farms. These shortcomings arise from cross-sectional study designs and poor record keeping practiced by many such farmers. Furthermore, there is a large diversity of AMU metrics, and it is not clear how these metrics relate to each other. We performed a longitudinal study on a large cohort of small-scale chicken farms (N=102) in the Mekong Delta (Vietnam), an area regarded as a hotspot of AMU, from October 2016 to May 2018. We collected data on all health-supporting medicine products administered to 203 small-scale flocks, with the following aims: (1) to describe the types and quantities of antimicrobial active ingredients (AAIs) used; (2) to describe critical time points of AMU; and (3) to compare AMU using three quantitative metrics. These were: (1) weight (amount) of AAIs related to bird weight at the time of treatment (mg/kg at treatment); (2) weight of AAIs related to weight of birds sold (mg/kg sold); and (3) ‘treatment incidence’ (TI), defined as the number of daily doses per kg of live chicken (ADDvetVN) per 1,000 days. A total of 236 antimicrobial products were identified, containing 42 different AAIs of 13 classes. A total of 76.2% products contained AAIs of ‘critical importance’ according to WHO. On average, chickens consumed 791.8 (SEM ±16.7) mg/kg at treatment, 323.4 (SEM ±11.3) mg/kg sold and the TI was 382.6 (SEM ±5.5) per 1,000 days. Oxytetracycline and colistin were the most used AAIs based on mg/kg sold and TI, respectively. AMU was more common in the early phases of the production cycle, and was high skewed, with the upper 25% quantile of flocks accounting for 60.7% of total AMU. The observed discrepancies between weight- and dose-based metrics were explained by differences in the strength of AAIs, mortality levels, and the timing of administration. These results suggest that AMU reduction efforts in chicken production should preferentially target the brooding period, while restricting access to antimicrobials of critical importance for human medicine.